Construction of pH-sensitive sodium alginates/sodium carboxymethyl cellulose/zeolite P composite hydrogel microspheres loaded with potassium diformate. Issue 1 (2nd January 2023) - Fu, Bei; Yang, ZhongXin; Li, Xing; Xu, WenQin; Pan, GuangHua; Chen, NanChun; Xie, QingLin; Wang, XiuLi
Abstract: As a substitute for feed antibiotics, potassium diformate (KDF) can effectively inhibit bacterial overgrowth in the gastrointestinal tract. To avoid the sudden release of KDF in the stomach, this article proposes a new controlled drug delivery system for controlled drug release. In this system, P-type zeolite molecular sieve (Zeolite P) and drug KDF are combined and embedded into the hydrogel microspheres of sodium alginate (ALG) and sodium carboxymethyl cellulose (CMC). In addition, ALG/CMC/Zeolite P composite hydrogel microspheres were prepared with Ca 2+ as the crosslinking agent. The structure, composition, morphology, and thermal stability of the hydrogel microspheres were systematically characterized. The effect of the composition ratio of ALG and CMC on the swelling properties of the hydrogel microspheres was also investigated. The results revealed that ALG and CMC form a hydrogen bond and chelate with Ca 2+ to form a double crosslinked network structure. Thus, Zeolite P can be effectively encapsulated in the hydrogel microspheres to form a dense three-dimensional network structure. Particularly, Zeolite P helps in improving the thermal stability of microspheres, balance the swelling properties, and control the release of KDF. The drug release results and release kinetics reveal that the ALG/CMC/Zeolite P composite hydrogel has higher drug release in an environment with pH 7.4. The release kinetics follow the Ritger–Peppas model and the first-order kinetic model, which indicates that the composite hydrogel has good specific pH sensitivity. In vitro antibacterial experiments revealed that the composite hydrogel microspheres have broad-spectrum antibacterial activity, and certain inhibitory effects on Escherichia coli, Staphylococcus aureus, and Bacillus subtilis . Graphical Abstract: UF0001